Development of Polyethersulfone (PES)/Silver Nanoparticles (AgNPs)/Polyethylene Glycol (PEG) Nanofiltration Membrane - Johary F.; Jamaluddin N.A.; Rohani R.; Hassan A.R.; Sharifuddin S.S.; Mohd Hafez Mohd Isa (American Institute of Physics Inc., 2024)
Indexed by Scopus